Advanced course for Asia & North Africa on conservation agriculture: Gateway for sustainable agrifood systems - Chakraborty, Debashis; Gathala, Mahesh Kumar; Rana, D.S.; Kalvanya, K.; Singh, Y. (International Maize and Wheat Improvement Center, 2024)
The Conservation Agriculture (CA) practices with increased acceptance across the globe are being considered as harbinger for sustainable intensification of smallholder production systems. Its positive impact on natural resources, and resilience to climate change effects are widely acknowledged. In developing world and specially Asia and Africa, CA is a relatively new introduction and hence capacity development is vital for development, adaptation, and scaling CA based technologies for impact at scale on smallholder farmers in these regions. Therefore, an advanced and practical course on conservation agriculture was organized to offer a unique capacity development opportunity to the scientific community associated with natural resource management research for development (NRMR4D). The advanced course on CA in Asia & North Africa was initiated during 2010 and 11th in the series was organized by CIMMYT- BISA-ICAR under the aegis of CGIAR Research Programs on WHEAT, MAIZE, TAFSSA and ICAR-CA and F2R CWANA. This course links the advances and multidisciplinary approach for sustainable intensification of maize and wheat-based systems and cereal & legume-based systems in general. The technologies and strategies for restoration of natural resource and climate resilient production systems with vast expertise of CIMMYT, ICAR & BISA researchers and partners across Asia, Africa, and Americas. Keeping in view the high response, the course has become a regular flagship activity wherein selected young men and women researchers from NARS as well as international organizations and NGOs across Asia and North Africa involved in CA based sustainable intensification can be benefited.